Exploring the multifaceted influence of affective factors on English reading comprehension among senior high school students - Fitria, Maulida Faizzatul; Usadiati, Wahyuningsih; Rusfandi, Rusfandi (Psychology, Evaluation, and Technology in Educational Research, 2024)
Existing research has emphasized the significance of cognitive factors in facilitating reading comprehension. Nevertheless, there is limited understanding of how affective factors contribute to this aspect of English learning, particularly within the Indonesian context. This study examines the contribution of affective factors (learning motivation, academic self-efficacy, and self-concept) to English reading comprehension among senior high school students. Adopting a correlational research design, it analyzed data from 136 eleventh graders using multiple regression analysis. The data was collected using the Reading Comprehension Test, Learning Motivation Scale, Academic Self-Efficacy Scale, and Self-Concept Scale. The analysis revealed a significant positive contribution of learning motivation to reading comprehension, accounting for approximately 8.9% of the variance (t-value of 3.626, p-value of 0.000), while academic self-efficacy explained about 4.4% (t-value of 2.484, p-value of 0.014). However, self-concept was found to have no significant effect on reading comprehension (t-value of -0.022, p-value of 0.982). Collectively, learning motivation and academic self-efficacy explicated around 11.9% of the variability in reading comprehension scores, as evidenced by an F-statistic of 9.021 and p-value of 0.000. The study concludes that affective factors are crucial in reading instruction. It suggests educators integrate strategies fostering motivation and self-efficacy to enhance reading comprehension.